(untitled) (Perner’s Contacts, 2014)
Coupling of railway vehicles is an integral part of the railway traffic. Is a risk of incorrect approach of drive vehicle to standing towing vehicles and the possibilities of creation of large shocks leading to greater wear of bumpers or the occurrence of accident. Another dangerous situation arises in connection with a limited view of train driver from vehicle. There is a risk of personal injury or death for people, which is located in this area. This risk has been exacerbated in the case of using the remote control vehicle e.g. for shunting on the siding. ASL device developed at VSB - Technical University of Ostrava, Institute of Transport in cooperation with MSV Electronics, Ltd., aforementioned risk significantly reduced or completely eliminated.